Upaya Kepala Sekolah dalam Peningkatan Mutu Pendidikan Melalui Komponen Pembiayaan di MTs Daarul Ulum Sukaraja Kabupaten Garut - Syifa Aghnia Zaenal; Nan Rahminawati; Fitroh Hayati (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
MTs Daarul Ulum Sukaraja, as a private school with limited educational funding, has been able to optimize all its financial resources to improve the quality of education. This study aims to analyze the efforts of the school principal in managing school financing to enhance educational quality at MTs Daarul Ulum Sukaraja. The researcher used a qualitative approach and a descriptive method. The data sources for this research were obtained through purposive sampling. The informants in this study included the school principal, vice principal, treasurer, teachers, and other staff members. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that MTs Daarul Ulum is a private school accredited with an